1999
DOI: 10.1071/ar98014
|View full text |Cite
|
Sign up to set email alerts
|

The current and future role of near infrared reflectance spectroscopy in animal nutrition: a review

Abstract: This paper aims to present an overview of the research into and application of near infrared reflectance spectroscopy (NIRS) in relation to animal nutrition over the last decade or so. Emphasis is placed on the developments in the characterisation of forages, although aspects of non-forage feeds are also considered. The changing remit of animal nutrition in relation to human food production and the environment is placing increasing requirements on feed characterisation to be more physiologically meaningful. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 53 publications
1
83
0
7
Order By: Relevance
“…This is mainly because of the variation in range and quantity of raw materials which may exhibit different spectral characteristics for a compound feed with apparently the same chemical composition (Givens & Deaville, 1999). Aufrère et al (1996) stated that NIRS is not widely used for concentrates and compound feeds as a large number of samples are required for the calibration.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because of the variation in range and quantity of raw materials which may exhibit different spectral characteristics for a compound feed with apparently the same chemical composition (Givens & Deaville, 1999). Aufrère et al (1996) stated that NIRS is not widely used for concentrates and compound feeds as a large number of samples are required for the calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Also tests need to be done with multiple samples frequently to profile a complete silo of feed and forage, which could impact operating costs. In the last few years, nondestructive testing methods such as Near Infrared Spectroscopy (NIR) has gained popularity for feed testing due to its rapid and inexpensive characteristics (Fulgueira et al, 2007;Givens & Deaville, 1999;Rasby et al, 2008;Undersander, 2007) …”
Section: Wet Chemistry Testingmentioning
confidence: 99%
“…The chemical composition of feed rations is typically determined by using either wellestablished wet chemistry tests or by Near Infrared Spectroscopy (NIR) (Ball et al, 2001;Cozzolino & Moron, 2004;Givens & Deaville, 1999). Conventional wet chemistry analysis is time-consuming, labor-intensive and expensive (Osborne, Fearn, & Hindle, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (Eckman et al, 1983;Park et al, 1997;Steen et al, 1998;Ward et al, 1982) concluded that NIRS could be used to measure diet digestibility, voluntary DM intake and production responses in ruminants fed forage-based diets as accurately as can be done with conventional laboratory analyses. Many research groups and studies have successfully developed calibrations to measure a wide range of forage quality attributes (Ramana Sharma et al, 2010;Smith and Flinn, 1991;Stimson et al, 1991), animal response (Abrams et al, 1987) and voluntary intake (Agnew et al, 2004;Deaville and Flinn, 2000;Givens and Deaville, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS for analysis including of feedstuffs (Givens and Deaville, 1999;Williams and Norris, 2001;Williams, 1975) is based on the measurement of the absorption of light in the near infrared range (700-3000 nanometres (nm) region) which is closely related to important chemical bonds (OH, NH and CH) (Deaville and Flinn, 2000;Dixon and Coates, 2010).…”
Section: Introductionmentioning
confidence: 99%